Inovasi Packaging dan Strategi Pemasaran Keripik Singkong Abadi Kriuk sebagai Upaya Peningkatan Daya Saing UMKM - Cilsy Mira Mawarni; Hani Fabiola Rustiana; Levina Konita Kusumadani; Ming Ming Lukiarti (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Background: The Business Internship Program (KKU) is a community service program aimed at supporting the development of Micro, Small, and Medium Enterprises (MSMEs) through mentoring and empowerment. The Abadi Kriuk Cassava Chips MSME, which operates in the snack food industry, faces several challenges, such as limited promotion and marketing, unattractive product packaging, and suboptimal use of digital media as a marketing tool. These conditions can hinder business development and product competitiveness in the market. Objective: This community service activity aims to increase the competitiveness of Abadi Kriuk Cassava Chips MSMEs through the development of digital marketing strategies, product packaging innovation, and expansion of promotional media to increase market reach Methods: The implementation of the activities was carried out through several stages, namely: 1) observation and interviews to identify business conditions and problems faced; 2) SWOT analysis as a basis for compiling a mentoring program; 3) digital marketing mentoring through the creation of social media accounts and business locations on Google Maps; and 4) creation of promotional media in the form of packaging designs, product catalogs, posters, and promotional banners. Expected Results: This initiative is expected to provide MSMEs with more optimal digital promotional media, more attractive and informative product displays, and a broader marketing reach. Furthermore, this initiative is expected to increase product sales, strengthen the company's image, and support the development of Abadi Kriuk Cassava Chips, making them more widely known.